AKAR PERMASALAHAN KEMISKINAN MASYARAKAT PESISIR KECAMATAN SASAK RANAH PASISIE DI KABUPATEN PASAMAN BARAT - Yulia Anas (Universitas Negeri Padang, 2013)
28% of 16.9 million population from 8,090 coastal village in Indonesia lived under the poverty line with the poverty headcount index 0.28 (BPS, 2010). The proportion the poor family in West Pasaman District is 45.1% which is 19% out of this part are lived in the coastal area. This purposes of this research are to analyze pattern and behaviour and the roots of the coastal area poverty. The result of this research should be a framework of the strategy and model for empowering the poor in coastal area, as a policy guidelines for poverty reduction program in Pasaman District. We found that pattern and behaviour of the poor in coastal area as; low level of education, avarage family member is 3 people in a family, 54,2% have access to health facility infrastructure, 74.5% are independent workers with avarage working hour in a week is 6 hour. The consumption behaviour of the coastal poor family catogarized as good. The roots of the poverty problem in this area are divided into two broad category, internal and external. The internal factors such as; low level of education, consumptive consumption behaviour, and cultural factors. External factor such as; inapropriate poverty reduction program, climate/wheater condition, monopolized market by the landlord for their product/output.